A Novel Framework to Evaluate Changes in Access to and Costs of Trade Finance - Marc Auboin; Eddy Bekkers; Dario De Quarti (Center for Economic Studies and ifo Institute (CESifo), 2023)
In this paper we integrate the costs of trade finance in a computable general equilibrium (CGE) model to evaluate the trade and output effects of counterfactual policy experiments on costs of and access to trade finance. The costs of financing international trade consist of two components: the financial costs and the costs associated with the risk of goods not being delivered, considering risk aversion of traders. These costs are determined for four ways to finance international trade (cash-in-advance, trade loans, letters of credit, and exports financed with internal working capital). Trade finance costs are a weighted average of the costs under the four different ways of financing. The framework is applied to trade of four ECOWAS countries employing data collected on financial costs, costs of risk and trade finance instrument shares through a comprehensive bank survey in these countries complemented with data from the literature. Counterfactual experiments on increases in the availability of letters of credit and trade loans and the costs of these instruments show that raising the shares and costs to African averages would increase trade of the four ECOWAS countries by about 11%. The framework is generic and can be applied to other countries.
Keywords: G58; F10; F14; F39; G21; 330; trade credit; international trade; financial institutions; general equilibrium simulations